The Effect of Odd Price on Purchasing Decisions Mediated by Processing Fluency - Kholifah, Kholifah; Mahyuzar, Hari (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Setting odd prices is one of the pricing strategies applied in retail. Setting odd prices can help one of their goals, which is to get more customers. It is a tool that companies use to influence consumer buying decisions. Consumer purchasing decisions are a reason for how consumers determine the choice of purchasing a product in accordance with their needs, desires, and expectations so that it can lead to satisfaction with product dissatisfaction and odd prices can have an impact on setting odd prices because it can make consumers feel satisfied and benefited and can lead to customer satisfaction. Ease of calculation fluency (processing fluency) will change their price perception and increase purchase intention for a final price that is consistent between the original price and the selling price is much cheaper than under inconsistent conditions, even though the magnitude of the discount under conditions of consistent final prices is lower than under inconsistent final price conditions. This research is a quantitative study and the respondents in this study were 100 respondents. In this study, the samples were taken by means of nonprobability sampling, namely by accidental sampling technique. Based on data analysis, it is known that there is an effect of odd prices on purchasing decisions, there is an effect of processing fluency on purchasing decisions and processing fluency mediates the relationship between odd prices and purchasing decisions.